Intervensi Kemanusiaan dan Kedaulatan Negara : Perspektif Pancasila dalam Hukum Internasional - Alyza Nur’aini Choirunnisa; Winda Dwi Astuti; Soraya Khoirun Nisa’; Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Humanitarian intervention is often seen as an effort to protect civilians from human rights violations, but it often clashes with the principle of state sovereignty in international law. This research evaluates the alignment of humanitarian intervention with the values of Pancasila as an ethical and moral footing in international policy. The research uses a qualitative method with a case study approach; data is obtained from a literature study that includes academic documents, journals, reference books, and diplomatic reports, then analyzed descriptively-analytically to reveal the views of Pancasila in the practice of international law. The results show that although intervention has noble aims, its implementation often collides with the principle of non-intervention and the principle of state sovereignty. The values of Pancasila, especially fair and civilized humanity and social justice, can be used as a moral foundation to assess the legitimacy of intervention, but its application in international norms is still constrained by political interests and power imbalances between states. The conclusion of this study is that Pancasila offers a potential ethical framework for more just humanitarian interventions, but diplomacy and policy advocacy efforts are needed to strengthen the position of developing countries in formulating international norms that respect sovereignty while protecting human rights.